Psychometric evaluation of the healthy aging activity engagement scale - Lu, Tingting; Kong, Linghui; Zhang, Huijun (Frontiers in Public Health, 2022)
Objective: The aim of this study was to translate the Healthy Aging Activity Engagement Scale (HAAE) into Chinese and validate its psychometric properties in the middle-aged and elderly population. Methods: A total of 424 middle-aged and elderly people were recruited from China's Jiangsu Province, Liaoning Province, Shandong Province, and Heilongjiang Province. Cronbach’s a coefficient, split-half reliability, and test-retest reliability were used to evaluate the reliability of the tranlated scale. Expert consultation was used to evaluate the content validity of the tranlated scale . Exploratory factor analysis (EFA) and confirmatory factor analysis(CFA) were used to evaluate the structural validity of the scale. Results: The Cronbach’s α coefficient of the Chinese version of HAAE was 0.965. and the Cronbach’ s α coefficient of the dimensions ranged from 0.898 to 0.957. The split-half reliability was 0.807, and the test-retest reliability was 0.850. The content validity index of the scale (S-CVI) was 0.969. A total of three common factors were extracted from the EFA.The CFA validated the explored 3-factor structure, and the indicators were well fitted.(χ2/df=1.393, comparative fit index=0.982, goodness- of- fit index=0.911. Tucker- Lewis Index=0.981 and root mean square error of approximation=0.030). Conclusion: The translated Chinese version of HAAE had suitable reliability and validity in the middle-aged and eldely population. The translated scale will be used to evaluate the level of healthy aging among middle-aged and elderly people in Chinese mainland. Furthermore, It also can provide some health advice for clinical patients.